A new, expanded approach to pediatric cardiology fellowship orientation. (September 2018) - Burstein, Danielle S.; Mille, Felina K.; Cohen, Meryl S.; Ravishankar, Chitra
Abstract: Background: Because of limited and varying resident exposure to pediatric cardiology, rapidly acquiring the necessary knowledge, clinical and technical skills can be overwhelming for incoming pediatric cardiology fellows. To address this, we developed a pediatric cardiology fellowship orientation at the beginning of fellowship using an extended orientation model. Methods: We designed and implemented a three-week extended orientation for all rising first year pediatric cardiology fellows at our institution to take place the first month of their training. The extended orientation consisted of: 1) daily lunchtime didactic sessions focused on general pediatric cardiology topics; 2) hands-on echocardiography experience (total 4.5 days) and high fidelity simulations focused on cardiac emergencies, extracorporeal membrane oxygenation, and cardiac palliative care; and 3) day-long precepted experiences in core clinical rotations. Pre- and post-extended orientation knowledge self-assessment results were compared using paired t -tests. Results: Due to protection from clinical duties during the three-week extended orientation period, all seven first-year pediatric cardiology fellows were able to participate in 100% of these sessions. After the extended orientation, participants demonstrated significant improvement in self-assessed knowledge in all clinical areas, with mean scores increasing from 45 ± 15% pre- to 74 ± 11% post-orientation (p ≤ 0.001). The greatest improvements occurred in echocardiography, catheterization, and cardiac anatomy. Based on a post-orientation feedback, additional education dedicated to electrophysiology, including EKG interpretation, arrhythmia management, and pacemaker basics, was recommended. Conclusion: A three-week extended orientation model for pediatric cardiology fellowship orientation at the beginning of fellowship effectively introduces incoming fellows to key clinical topics unique to cardiology. In the current educational era, this represents an alternative approach to the traditional orientation model. Facilitating full participation in these sessions without competing clinical duties may enable all fellows to start their training with the necessary clinical foundation and may improve their preparedness for clinical responsibilities. Highlights: Limited exposure to pediatric cardiology during residency requires rapid acquisition of clinical knowledge and skills. We propose a multi-modality, three-week extended orientation as an alternative to the traditional orientation model. Our novel model ensures full orientation participation for incoming fellows without competing clinical duties. This model effectively introduces incoming fellows to unique cardiology topics and may improve clinical preparedness.